KONSEP PENURUNAN AUTORITI (DELEGATION) MENURUT PERSPEKTIF ISLAM - Sarif, Suhaili (Jurnal Syariah, 2019)
Delegation is an important process in managing an organization. An effective delegation portrays a good manager-subordinate relationship that enables them to achieve organizational goals. This article discusses the concept and process of an effective delegation that should be implemented in each and every single organization.